A escrita negra de Solano Trindade: movimentos de resistência e modos de identidade da consciência poética - Silva, Denivaldo Matos Moreira Almeida e (2013)
This dissertation presents the contributions of poetry Solano Trindade for black literature, as well as the important presence of personal and collective memory of the black rhythm in the body of his poetry. Reading focuses on surveying the characteristics of folk art (music, dance, folk rhythms and cultural), and especially the ways identifiers word in our idealized black Brazilian land, under the Marxist style and unique aesthetic of the poet. It also seeks to investigate the relationship between the poetics of everyday Solano Trindade and african- Brazilian culture, with the backdrop of the myth and meaning. The main objective is to describe how is the search for identity african-Brazilian and identifying ways manifest in resistance movements in the composition of poetry Solano Trindade, the crossing of black literature with African myth. The hypothesis of the research confirms that the myth is the foundation for the reconstruction of black identity mediated representation, once freed from the laws of metaphysical ontology. As a result, it is evident the desubjectivation inaugurated by the poetic self awareness of the world incorporated into the idea of aesthetic in black voice of the poet Solano Trindade